Palmito Ranch : From Civil War Battlefield to National Historic Landmark - Ginn, Jody Edward, 1969-; McWhorter, William Alexander, 1975- (Book collections on Project MUSE., 2018)
"Opening with a crisp retelling of the principal military events that unfolded at Palmito Ranch, near the Confederate port city of Brownsville, Ginn and McWhorter go on to recount the determined initiative pursued by a team of stakeholders, organized largely through the efforts of the Texas Historical Commission, to study, document, and preserve this important Texas historic site. Now, after less than a decade of focused effort, visitors to the area may benefit from not only improved and expanded historical markers, but also a radio transmitter and a viewing platform, along with other interpretive aids. All this is due to the campaign spearheaded by McWhorter, Ginn, and a cohort of dedicated volunteers and professionals. The objective, as McCaslin's foreword emphasizes, is to 'enhance Texans' understanding of their state's role in the Civil War.'"